Stem Cells for the Treatment of Neurological Disorders - Rao, Mahendra S.; Khanna, Aparna; Shin, Soojung (CNS & Neurological Disorders - Drug Targets, 2008)
Embryonic stem cells (ESC) are a source of renewable cells, which possess a phenomenal potential to differentiate into a myriad of cell types. Thus, ESCs offer a potentially unlimited supply of cells, which can be deployed in developing cell-based therapies. The in vitro differentiation capacity of ESC into derivatives of the neuronal lineage has been demonstrated and the functionality of the ESC derived neuroprogenitors, upon transplantation into in vivo models has been substantiated. In this review, we discuss various approaches to directing ESC towards neural lineages and protocols for sorting and selection of differentiated progenies. We examine in particular in vitro differentiation of ESC to mid-brain dopaminergic (DA) neurons and glial cells and the potential issues related to the transition to the clinic.
Keywords: transplantation